EDUCATION DINIYAH POLICY IN THE SCOPE OF AL-BAROKAH ISLAMIC BOARDING SCHOOL DURING THE COVID-19 PANDEMIC - Muhammad Bustanul Arifin; Firmansyah Firmansyah; Akhmad Sahrandi (Research Department (Lemlit) Islamic Institute of Darullughah Wadda’wah Bangil, Pasuruan, 2020)
Abstract Diniyah education in Islamic boarding schools is a program that must be undercontrolled and further improved both in quality and quantity, in order to improve the students attention in studying for their future. To accomplish that goal, we need supporting factors such as diniyah, Al-quran readings, bandongan, sorogan and the role of ustadz as mentors as guides and role models for students. The purpose of this research is to increase the investment of the excellent children, have good character and morality, broad -minded by bringing Islamic values, salaf as exemplified by previous scholars. This research uses qualitative methods based on real theories. it uses observation techniques to observe the surrounding conditions, especially within the scope of the Islamic boarding school. The expected results of this study are: 1) existing policies in madrasah diniyah are run properly to accommodate children who in the future continue the relay of the struggle of the previous leader, who have good morality, noble character, based on the values of Islamic teachings. Policies in the diniyah may be different from before because this country is still struggling from the covid virus which has not ended until to day.